Ferruginous bodies resolved by synchrotron XRF in a dog with peritoneal malignant mesothelioma. - Pascotto, Ernesto; Gianoncelli, Alessandra; Calligaro, Carla; Marcuzzo, Thomas; Melato, Mauro; Rizzardi, Clara; Pascolo, Lorella (Environ Sci Pollut Res Int, 2018)
Mesothelioma is a malignant tumor mainly correlated to occupational asbestos exposure. Rare reports describe its occurrence also in animals, mainly linked to asbestos in the environment. Asbestos exposure is demonstrated by the appearance of characteristic histological hallmarks: asbestos containing ferruginous bodies that are iron-based structures forming around fibers and also other dust particles. Here we present a clinical case of a suspect of mesothelioma in the peritoneum of a dog with parallel histological observation of ferruginous bodies. To possibly correlate the dog tumor to environmental exposure, we performed X-ray fluorescence (XRF) analyses at two different synchrotrons to resolve the ferruginous bodies' composition. While the histological examination diagnoses a tubulo-papillary mesothelioma, the XRF analyses show that ferruginous bodies contain Si particles, resembling formations of exogenous origin; however, the morphology is unlikely that of asbestos fibers. We speculate that the peritoneal mesothelioma of this dog could be related to environmental exposure to non-asbestos material.
Keywords: Animals; Asbestos; Dogs; Environmental Exposure; Immunohistochemistry; Iron; Lung; Lung Neoplasms; Male; Mesothelioma; Peritoneal Neoplasms; Silicon; Spectrometry, X-Ray Emission; Synchrotrons

Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.